2007
DOI: 10.1007/s00268-006-0907-6
|View full text |Cite
|
Sign up to set email alerts
|

Central Lymph Node Dissection in Differentiated Thyroid Cancer

Abstract: Evidence-based recommendations support CLND for PTC in patients under the care of experienced endocrine surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
203
2
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(222 citation statements)
references
References 69 publications
9
203
2
8
Order By: Relevance
“…In this study, the permanent hypoparathyroidism was documented in 6.5% for group A and 9.4% for group B patients which was much less than that reported by Tartaglia et al, 2014 25.4% of patients who underwent TT + CND, within the range reported by White et al, 20070-14.3% while Pereira et al, 2005Choi et al, 2011;Popadich et al,2011;Wang et al, 2013;and Lee et al, 2015 reported only 2%, 3% ,0.8%, 4.6% and 3.3% permanent hypoparathyroidism respectively. Temporary hypoparathyroidism was (Tartaglia et al, 2014), 6% (Wang et al, 2013) and 9.7% (Popadich et al, 2011) but sometimes as high as 60% (Pereira et al, 2005).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…In this study, the permanent hypoparathyroidism was documented in 6.5% for group A and 9.4% for group B patients which was much less than that reported by Tartaglia et al, 2014 25.4% of patients who underwent TT + CND, within the range reported by White et al, 20070-14.3% while Pereira et al, 2005Choi et al, 2011;Popadich et al,2011;Wang et al, 2013;and Lee et al, 2015 reported only 2%, 3% ,0.8%, 4.6% and 3.3% permanent hypoparathyroidism respectively. Temporary hypoparathyroidism was (Tartaglia et al, 2014), 6% (Wang et al, 2013) and 9.7% (Popadich et al, 2011) but sometimes as high as 60% (Pereira et al, 2005).…”
Section: Discussioncontrasting
confidence: 45%
“…Putting in mind that pCND was advised by the European Thyroid Association, the British Thyroid Association, and the American Thyroid Association (Pacini et al, 2006;Grubbs et al, 2007) and its benefit in the accurate staging of the tumor, which may guide subsequent treatment and follow-up, in addition to decreasing the recurrence of PTC, improving disease-specific survival, and significantly reducing levels of serum thyroglobulin, increasing the rate of athyroglobulinemia (White et al, 2007) so pCND was done in all patients (including level VII in group A) of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been generally accepted that the majority of PTMC patients has an excellent prognosis. However, this view has been challenged with new researches reporting increased local recurrence rates (White et al, 2007) and reduced survival with regional LNM (Hughes et al, 2010). For PTMC, cervical lymph node metastases are common, with an incidence between 30% and 60% (Hay et al, 2008;He et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For White et al, 2007 the rate of permanent hypoparathyroidism after total thyroidectomy (TT) with prophylactic CND is between 0% and 14.3%.…”
Section: Ihab Samy Fayekmentioning
confidence: 99%